Questionnaire Translation and Validation of Problem-Focused Coping in Increasing Work to Family Enrichment in Context of Laos : https://doi.org/10.69692/SUJMRD0802166 - KEOBOUALAPHETH, Soulideth; Sabil, Surena; Kock Wah, Tan (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This study aims to translate and validate a questionnaire of problem-focused coping in increasing work to family enrichment in the context of Laos. The questionnaire is translated by using forward and backward translation process with two Lao bilingual translations: then this questionnaire is evaluated through three validity criteria (content validity, face validity, and construct validity) and reliability process. The findings show that the questionnaire translation is available locally, culturally acceptable, and conceptual equivalence for Lao language. Lao questionnaire version is fulfilled acceptable standards of validity and reliability analysis. This study suggests that the Lao questionnaire version is locally accepted to proceed for further actual study in Lao context.